Stable isotopes of H, C and N in mice bone collagen as a reflection of isotopically controlled food and water intake*. Issue 2 (4th March 2019) - Topalov, Katarina; Schimmelmann, Arndt; Polly, P. David; Sauer, Peter E.; Viswanathan, Suresh
ABSTRACT: 2 H/ 1 H ratios in animal biomass reflect isotopic input from food and water. A 10-week controlled laboratory study raised 48 mice divided in two generations (8 mothers Mus musculus and their offspring). The mice were divided into four groups based on the combination of 2 H, 13 C, 15 N-enriched and non-enriched food and water. Glycine, the most common amino acid in bone collagen, carried the 2 H, 13 C, 15 N-isotopic spike in food. ANOVA data analysis indicated that hydrogen in food accounted for ∼81 % of the hydrogen isotope inventory in collagen whereas drinking water hydrogen contributed ∼17 %. Air humidity contributed an unspecified amount. Additionally, we monitored 13 C and 15 N-enrichment in bone collagen and found strong linear correlations with the 2 H-enrichment. The experiments with food and water indicate two biosynthetic pathways, namely (i) de novo creation of non-essential amino acids using hydrogen from water, and (ii) the integration of essential and non-essential amino acids from food. The lower rate of isotope uptake in mothers' collagen relative to their offspring indicates incomplete bone collagen turnover after ten weeks. The variance of hydrogen stable isotope ratios within the same cohort may limit its usefulness as a single sample proxy for archaeological or palaeoenvironmental research.